(untitled) (AYUSHDHARA, 2025)
Haemorrhoids, are described as swollen blood vessels in the anal canal, India has one of the highest rates of piles in the world, with about 11% of the prevalence rate. The prevalence of piles is higher in urban areas, and men are more likely to be affected than women. And this condition is one of the most common conditions seen in Shalya tantra OPD. Haemorrhoids typically results from persistent straining during bowel movements, which can occur in cases of constipation or diarrhoea. According to Ayurveda, haemorrhoids can be correlated with Arsha based on the Lakshana. Due to the limitations of standard medical treatments and a high rate of hesitance regarding surgical options, there is an increasing demand for alternative approaches to manage this condition. Thrombosed Pile mass is one among the complications of the haemorrhoids. It is an extremely painful condition characterised by dark purple or black solid mass and the anal margin becomes oedematous with severe pain. Pain may continue for a week or so until the oedema subsides and the thrombus is absorbed. In this case report a 30 year old male patient a known case of haemorrhoid came to Shalya tantra OPD at Dr.BRKR Government Ayurvedic hospital, Hyderabad with sudden onset of severe pain in anal region, Reddish and slightly bluish colour solid pile mass. And it was successfully treated with oral Ayurvedic medicine Lasunadi vat, Arshohara vati and Panchasarkara churna and without any surgical intervention. After one week of medication patient got complete relief from the symptoms. This paper is aimed to highlight and to know about properties of Lasunadi vati and its effect on thrombosed pile mass.